2013
DOI: 10.1111/bjh.12297
|View full text |Cite
|
Sign up to set email alerts
|

CEBPA double‐mutated acute myeloid leukaemia harbours concomitant molecular mutations in 76·8% of cases with TET2 and GATA2 alterations impacting prognosis

Abstract: SummaryAcute myeloid leukaemia (AML) with CEBPA mutations is listed as a provisional entity in the current World Health Organization classification. A difference in clinical outcome between single-(sm) and double-mutated (dm) cases has been reported, whereupon CEBPAdm cases were shown to be associated with better overall survival (OS). The occurrence and prognostic impact of concomitant molecular mutations in addition to CEBPAdm has not been assessed until now with exception of GATA2 mutations. Here, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
89
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 27 publications
9
89
5
1
Order By: Relevance
“…However, we confirmed no prognostic impact of GATA2 mutations (n 5 25) compared to wild-type (n 5 62) in our cohort of CEBPA dm AML [8,9] (22 vs. 58 and 10 vs. 16) with a trend similar of better outcome in CEBPA dm with GATA2 mutations compared to wild-type [5,6] (18 vs. 62). Furthermore, our study provided first evidence that homozygous CEPBA mutations have a similar gene expression signature as CEPBA dm and thus may be considered as equivalent.…”
supporting
confidence: 44%
See 3 more Smart Citations
“…However, we confirmed no prognostic impact of GATA2 mutations (n 5 25) compared to wild-type (n 5 62) in our cohort of CEBPA dm AML [8,9] (22 vs. 58 and 10 vs. 16) with a trend similar of better outcome in CEBPA dm with GATA2 mutations compared to wild-type [5,6] (18 vs. 62). Furthermore, our study provided first evidence that homozygous CEPBA mutations have a similar gene expression signature as CEPBA dm and thus may be considered as equivalent.…”
supporting
confidence: 44%
“…Many ITP patients, particularly patients with anti-GP Ib-IX autoantibodies, do not respond to conventional treatments such as steroids, intravenous immunoglobulins, or splenectomy [4][5][6][7][8]. Also the role of new therapies like thrombopoietin agonist are unclear and not without risks [9].…”
Section: Sialidase Inhibition To Increase Platelet Counts: a New Treamentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Gene expression studies have shown that CEBPA bi samples, but not specimens with CEBPA monoallelic mutations, have a distinctive gene expression profile (GEP), [15][16][17][18] and analyses of small series indicated a possibility that this profile is shared by some atypical CEBPA bi AML. 15 Mutations in genes such as GATA2, WT1, and TET2 have been described thus far in CEBPA bi specimens, [19][20][21][22] including 6 specimens reported in The Cancer Genome Atlas cohort. 7 We previously used comparative transcriptomic approaches to report the mutational and transcriptional landscapes of MLL,…”
mentioning
confidence: 99%